2011
DOI: 10.1159/000327525
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cells in Liquid-Based Cervical Cytology: A Diagnostic Pitfall Solved by Preparing Cytohistology from the Residual Thin Layer Sample

Abstract: Objective: It was our aim to assess the usefulness of cytohistology in cervical thin layer brush samples with problems in the differential diagnosis of endometrial cells. Study Design: This study reveals the cytological, cytohistological and immunohistochemistry findings of 8 cases suspicious of adenocarcinoma in situ (AIS)/adenocarcinoma (AC) in cervical liquid-based cytology (LBC) preparations that turned out to be normal endometrial cells. Results: All 8 cervical LBCs featured endometrial and atypical endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In addition, endometrial reactive changes were included, as well as premalignant and malignant changes of the endometrium. This was not only to monitor the endometrial changes in the cases assessed, but also as a control group for endocervical gland changes, to avoid misinterpretation and overinterpretation, which have been noticed in previous works as reported by Schnatz et al ( 11 ) and Risse et al ( 12 ) that have described the dysplastic changes in the endocervical epithelium and atypical glandular lesions. The present study also included the vaccination status of individuals against HPV, as until now, to the best of our knowledge, the importance of vaccination has not been well understood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, endometrial reactive changes were included, as well as premalignant and malignant changes of the endometrium. This was not only to monitor the endometrial changes in the cases assessed, but also as a control group for endocervical gland changes, to avoid misinterpretation and overinterpretation, which have been noticed in previous works as reported by Schnatz et al ( 11 ) and Risse et al ( 12 ) that have described the dysplastic changes in the endocervical epithelium and atypical glandular lesions. The present study also included the vaccination status of individuals against HPV, as until now, to the best of our knowledge, the importance of vaccination has not been well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The study group also did not include any cases of endocervical adenocarcinoma, another significant cervical lesion that may cause a diagnostic dilemma. However, it was recently demonstrated that cervical adenocarcinoma was successfully differentiated from endometrial cells by using cell block and an immunostain panel including p16 INK4a , Ki-67, and CD10 [3]. Furthermore, both p16 INK4a and ProEx C appear insensitive for detecting LSIL lesions, although the differential diagnosis is often straightforward based on cytologic features.…”
Section: Discussionmentioning
confidence: 99%
“…HCGs, are present. Several dysplasia-associated biomarkers have been used through immunohistochemistry in an attempt to distinguish precancerous or malignant HCGs from benign cell clusters [2,3]. Those markers include ProEx C, p16 INK4a , Ki-67, MCM2 (minichromosome maintenance protein 2), and TOP2A (DNA topoisomerase IIα) [reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation